2013
DOI: 10.1007/s10557-013-6457-x
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acids Increase Plasma Adiponectin to Leptin Ratio in Stable Coronary Artery Disease

Abstract: BackgroundGrowing evidence suggests a cardioprotective role of omega-3 polyunsaturated fatty acids (PUFA). However, the exact mechanisms underlying the effects of omega-3 PUFA in humans have not yet been fully clarified.PurposeWe sought to evaluate omega-3 PUFA-mediated effects on adipokines in patients with stable coronary artery disease (CAD) undergoing elective percutaneous coronary intervention (PCI).MethodsWe conducted a prospective, double-blind, placebo-controlled, randomized study, in which adiponectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 27 publications
0
34
1
1
Order By: Relevance
“…We did not detect any influence of 14-month administration of ω-3 PUFA on circulatory leptin concentration in patients with SCI, which is in line with the findings of Sneddon et al 33 who investigated this association in lean and obese men. By considering previous reports 30,31,34,35 that demonstrated increased adiponectin after ω-3 PUFA therapy and decreased leptin 30 concentration in patients with CVDs, this point is clarified that the effect of ω-3 PUFA is dependent on patients' background disorders. Weight was positively related with leptin concentration at the beginning of the trial (stage 0) but this association was attenuated only in the treatment group after receiving ω-3 PUFA while it remained significant in the placebo group till the end of the trial.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We did not detect any influence of 14-month administration of ω-3 PUFA on circulatory leptin concentration in patients with SCI, which is in line with the findings of Sneddon et al 33 who investigated this association in lean and obese men. By considering previous reports 30,31,34,35 that demonstrated increased adiponectin after ω-3 PUFA therapy and decreased leptin 30 concentration in patients with CVDs, this point is clarified that the effect of ω-3 PUFA is dependent on patients' background disorders. Weight was positively related with leptin concentration at the beginning of the trial (stage 0) but this association was attenuated only in the treatment group after receiving ω-3 PUFA while it remained significant in the placebo group till the end of the trial.…”
Section: Discussionmentioning
confidence: 75%
“…29 Some alterations in leptin and adiponectin concentrations have been reported after intervention with omega-3 fatty acids. Mostowik et al 30 showed increased adiponectin to leptin ratio with a 30-day administration of omega-3 fatty acids in patients with stable coronary artery disease. However, its effect on circulatory concentrations of leptin and adiponectin was not yet evaluated in spinal cord injured patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, an increased dietary consumption of fish was found to be associated with a reduced level of leptin [28]. Mostowik et al (2013) found that daily supplementation of 1 g/d of omega-3 fatty acid for 30 days significantly increased adiponectin level and adiponectin/leptin ratio as well as resulted in a significant reduction in leptin level [68]. The effect of omega-3 fatty acid on adiponectin and leptin levels is suggested to be a concomitant to its modulatory effects on cytokine and proinflammatory mediators [21].…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain n-3 polyunsaturated fatty acids (PUFAs), namely, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), decrease plasma triglyceride (TG) levels, arrhythmias, and inflammation, thereby ameliorating endothelial dysfunction [2,4]. The beneficial effect of n-3 PUFA intake on the metabolic profile of patients with T2DM and obesity has been reported [5].…”
Section: Beneficial Effects Of N-3 Fatty Acids Onmentioning
confidence: 99%
“…n-3 PUFAs accumulate in adipose tissue [4], so it could be hypothesized that some of their effects might partly be associated with improvements in adipose tissue function. Moreover, n-3 PUFAs have been found to ameliorate the low-grade inflammation in adipose tissue and regulate adipokine gene expression [4,6].…”
Section: Beneficial Effects Of N-3 Fatty Acids Onmentioning
confidence: 99%